BAHASA INDONESIA DAN PERJUANGAN BANGSA - Ni Nyoman Kertiasih (Universitas Warmadewa, 2019)
[Title: Indonesian language and the national struggle] This research aims to explain the formation of Indonesian as a national language, to explain that Indonesian is one of the tools of the nation’s struggle, and to explain the impact of Indonesian in the life of an anti-colonial nation. The data of this study were written material written during the struggle and after the struggle to drive out colonialism. The method used were a qualitative, analytical descriptive method, combined with a critical discourse analysis method. This research reveals that Indonesian language since its inception in 1928 has been understood as the language of the tool of the nation’s struggle. As a result, Indonesian language has influenced the attitude of the people, the nation in the face of colonialism. The community began to promote the use of Indonesian in the community, at school, and use Indonesian in various formal and informal meetings. People oppose using Dutch language that was previously required.